Profitability of large cardamom enterprise in Nepal?: Evidence from financial analysis - Keshav Prasad Shrestha (Journal of Agriculture and Natural Resources)
Large Cardamom is major exportable commodities prioritized by Ministry of Commerce and Supply in Nepal. However, no study has been reported for its financial analysis in the country. In this context, this study was designed and conducted in Ilam, Panchthar, and Taplejung to assess the profitability and financial viability of cardamom production. Primary data needed for the study were collected using structured survey schedule with 30 randomly selected cardamom growers from each selected district in May-July 2017. Primary information mainly compose information on investment cost, operating cost and revenue. Three Focus Group Discussions were also carried out in each district for triangulation of collected information. The secondary data were used for the Compound Annual Growth Analysis and financial analysis. The economic yield starts from the fourth year and remains similar up to 20 years. But, it was found from the study that with the proper management of the crop cultivation packages, about 10% yield starts from third year which have not been reported yet. The financial analysis result showed that, the Return on Investment was found about 160% with payback period of 4.09 years. Similarly, Net Present Value was assessed at NRs. 3,545,771 at 12% discount rate. Likewise, the Internal Rate of Return Benefit-Cost Ratio of cardamom production was 82.6% and 3.06, respectively. The sensitivity analysis with 20% increase in the cost of production and 20% decrease in the sold price rate also found profitable and viable enterprises as its Return on Investment is 34%, PBP is 5.64 years, NPV equals NRs. 2,154,393, IRR 57.6% and BCR found 2.06. Hence, the study recommends that this enterprise is very profitable and viable and farmer could invest confidently even its rate fluctuates very often.